Karakteristik Bioadsorben Limbah Ikan dengan Aktivator Kalsium Hidroksida (Ca(OH)2) - Satriawan, Dodi; Anggraeni, Melani; Aghni Bintang Sukono, Geo (Talenta Publisher (Universitas Sumatera Utara), 2025)
This research aims to conduct an initial analysis of the characteristics of bioadsorbent from fish waste which will be used as a pollutant adsorption. Fish waste was obtained from Tempat Pelelangan Ikan (TPI) in Cilacap district, Central Java. The fish waste obtained is dried by drying with solar thermal for 2 – 3 days. The carbonization process of fish waste is carried out by pyrolysis at a temperature of 550 oC for 4 hours until fish waste charcoal is produced. Charcoal is ground to 100 mesh size. The charcoal was then weighed 50 g and activated with 1 L of 5% Ca(OH)2 at a temperature of 70 oC with stirring at 350 rpm for 2 hours; 4 hours; and 6 hours. Analysis of characteristic bioadsorbent refers to SNI 06-3730-1995. Bioadsorbent from fish waste activated at an activation time of 6 hours has the best characteristics in terms of water content and ash content of 2,75% and 20,2% respectively, while the best characteristics in terms of volatile matter content and iodine absorption capacity are found in bioadsorbent without activation of 44,33% and 1.250,46 mg/g respectively.